DESCRIPTION OF CRITICAL THINKING IN SOLVING LINEAR I ALGEBRA PROBLEM BASED ON INITIAL ABILITY AND COGNETIVE STYLE OF UNDERGRADUATE STUDENTS OF MATHEMATIC EDUCATION STUDY PROGRAM - Harisa Safi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
The study aims at describing  (1) critical thinking of FIKT students (field independent with high category) students, (2) critical thinking of FDKT (field dependent with high category) students, (3) critical thinking of FIKS (field independent with medium category) students and (4) critical thinking of FDKS (field dependent with medium category) students. This study was descriptive study by employing qualitative approach. The research subjects were 4 students of class A1  of the second semester of Mathematics Education Study Program at UNM which categorized based on cognitive style by using the instrument of Group Embedded Figures Test (GEFT) and counting the IPK (Grade Point average) of mathematics courses on the first semester by differentiating two categories, namely high and medium categories, consisted of 2 field independent with high-medium category students and 2 field dependent with high-medium category students. Methods in collecting the data was critical thinking test, namely problem solving test of linear aquation systems and interviews. This study employed triangulation by comparing the data obtained through problem solving tests and interview. The result of critical thinking through problem solving was categorized based on critical thinking stage, namely clarification, analysis and solution strategy. The results of the study reveal that at the clarification stage,  the FIKT subject and FIKS subject had similarity in reading the questions briefly, understood  it directly and identifying the instructions of the questions; whereas, FDKT subject and FDKS subject read the questions repeatedly and only read instruction of the questions. At the Analysis stage,  FIKT subject and FIKS subject tended to be quick in abstracting and releting relevant information with supporting instruction of the questions, so it was quicker in concluding the method used to solve the problem. However, FDKT subject and FDKS subject tended to be longer in giving response,  so the method used was trial and error. At the solution Strategy, FIKT subject and FIKS subject applied the method used clearly and systematically; however, FIKS subject did mistake when determining k score using determinant (for the second question), unlike FDKT subject and FDKS subject which had difficulty when making conclusions based on question instruction and FDKS subject was also made mistake when determining  k score using determinant.